KEPUASAN KERJA, KOMITMEN ORGANISASI, ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) DAN PENGARUHNYA TERHADAP KUALITAS PELAYANAN PUBLIK - Meilina, Restin; Widodo, Mochamad Wahyu (LP2M Institut Teknologi dan Bisnis Asia Malang, 2017)
Service employees as the vanguard that plays an important role in determining the quality or not of public services. Efforts to provide quality public services can not ignore the factors of employee job satisfaction, organizational commitment employees, and organizational citizenship behavior (OCB) employees. This study aims to determine (1) the effect of job satisfaction on OCB, (2) influence of organizational commitment to OCB, (3) influence of job satisfaction on public service quality, (4) influence of organizational commitment to public service quality, (5) influence of OCB On the quality of public services, and (6) the indirect influence of job satisfaction and organizational commitment to the quality of public services through OCB. The study was conducted in 3 (three) sub-district offices in Kediri. Samples taken as many as 90 respondents with purposive sampling technique. Data collection through observation, interviews, and questionnaire dissemination. The data obtained were analyzed by path analysis. The result of the research shows that (1) job satisfaction has significant effect on OCB, (2) organizational commitment has significant effect to OCB, (3) job satisfaction has significant effect on public service quality, (4) organizational commitment has significant effect on public service quality, OCB has a significant effect on the quality of public services, (6) there is indirect influence of job satisfaction on the quality of public service through OCB, while for organizational commitment there is no indirect influence to the quality of public service through OCB.